On Some Ground State and Finite Temperature Properties of Mixed Valence Compounds Induced by Next to Next-Nearest-Neighbor (NNNN) Hopping (Bulletin of Pure and Applied Sciences – Physics, 2022)
In the present study, effects of next to next-nearest-neighbor (NNNN) hopping of d electrons in the crystal of mixed valence compounds has been discussed. For  convenient theoretical calculation and computer simulation within exact  diagonalization method, a small cluster of eight lattice sites is considered here to  investigate the valence transition through the study of the inter-site and on-site f-d correlation functions. Unusual magnetic behavior of mixed valence compounds has  also been examined. Antiferromagnetic (AF) order has been developed in the  compounds of rare earth elements with the addition of NNNN hopping interaction  within the extended Falicov-Kimball model. The extrapolation of the curves of the  reciprocal susceptibility (χ-1) intercept at a negative temperature which confirms AF  order in the system.